Institutional Synergies and the Fragility of Loan Funds - Emin, Mustafa; James, Christopher; Li, Tao; Lu, Jing (Review of Financial Studies, 2026)
Abstract There are two major institutional investors in the syndicated loan market: collateralized loan obligations (CLOs) and loan mutual funds. CLOs are closed-end funds while loan funds are open-end funds that issue claims that are redeemable on demand. In this paper, we examine whether CLOs provide arbitrage capital that contributes to the resilience of loan funds. We find that CLOs act as shock absorbers, providing liquidity through par-building trades when loan funds experience large outflows. However, CLO-provided liquidity is limited to par build–eligible loans, leading to potential flow-induced fire sales among par build–ineligible loans. (JEL G23, G38